Aplicações dos números complexos na geometria plana - Feitosa, Laércio Francisco (2013)
The teaching of Complex Numbers is based almost exclusively on an algebraic approach, although the geometric approach of complex numbers is contemplated in the study of its polar form (or trigonometric). The purpose of this paper is to present some significant applications of complex numbers in plane geometry, making thus a contrast to this view strictly algebraic and formal, that has traditionally characterized the teaching of these numbers. We'll cover some classical theorems of geometry and some geometric problems, evaluating the efficiency of complex numbers as a tool to demonstrate the theorems and results relevant to the resolution of such problems. Some of the theorems selected in our study were: Napoleon's Theorem, the Circle of Nine Points and Simson Line.